Drying models and quality analysis of sun-dried ciku - Chong, Chien Hwa; Law, Chung Lim; Cloke, Michael; Abdullah, Luqman Chuah; Wan Daud, Wan Ramli (Taylor & Francis, 2009)
Sun drying of ciku (Manilkara zapota) was carried out on different sample sizes to investigate the effects on drying kinetics. It was found that the maximum drying rates of sun-dried ciku decreased with larger product size. Three sunny days are needed to dry the ciku slabs to an average final moisture content of 0.2 g H2O/g dry mass. The results showed that hardness and chewiness of the dried samples were significantly different (p < 0.05) compared to fresh ciku slabs and commercial dried fruit. The color measurement of dried product showed that L* and b* values significantly decreased (p < 0.05), whereas the a* value increase was not significantly different (p > 0.05) compared to fresh ciku slabs. In addition, sun-dried ciku retained a total polyphenol content (TPC) that was relatively low (p < 0.05) compared to fresh ciku.